Building the economic backbone of the Belgian welfare state : infrastructure, planning and architecture 1945-1973 - Ryckewaert, Michael (Rotterdam : Uitgeverij 010, 2011)
The accommodation of a welfare state economy after 1945 profoundly changed the Belgian territory. Government support for private home ownership resulted in widespread suburban sprawl. This book investigates the new infrastructural and business backbone that supported this suburban realm. At first sight the history of the construction of the highway network, the establishment of a tissue of consumer goods industries and the transformation of Brussels' periphery into a capital region reads as an account of economic policy and investment decisions. However, upon closer scrutiny, various urban models and architectural paradigms left their mark on these endeavors.
Bibliografische referenties ; index
Keywords: Architecture and state -- History -- 20th century. -- Belgium; Architecture -- History -- 20th century. -- Belgium; City planning -- History -- 20th century. -- Belgium; Housing policy -- History -- 20th century. -- Belgium; Infrastructure (Economics) -- Belgium; Regional planning -- History -- 20th century. -- Belgium; Urban policy -- History -- 20th century. -- Belgium